The great divide: dividing the individual to preserve the salvation paradox - Griffith, David (2020)
The Church in its first several centuries split on whether Christ saved everyone or only a few, Universalism versus Exclusivism. In the sixth century, the Church settled the issue seemingly—Universalism was heretical. Within a century, Universalism became peripheral, but never perished and today regains Christian acceptance. The history of Universalism and Exclusivism from their beginnings to the present is reviewed along with what provoked the dissonance—Scripture gives contradictory accounts of salvation’s extent. That is, Scripture clearly says everyone is ultimately saved and just as clearly that everyone is not. Each side, of course, can exegete the competing account out of contention, but none has done so so convincingly that Exclusivism has been unseated from the orthodox position or that Universalism has been finished off entirely, because Scripture is clear in what it says if not what it means: Everyone is saved and not everyone is. The principle of noncontradiction, therefore, explains the dispute’s persistence. A few theologians have tried to accept the truth of contradictions, but they have been as successful as those trying to accept the truth of falsehoods. Unlike Exclusivism, Universalism, or the unintelligible, the thesis takes Scripture’s two accounts of salvation’s extent as a paradox. The approach taken is similar to that with other Scriptural paradoxes, such as God is both three and one or Christ is both God and man. These appear contradictory too, and heresies took them that way, but the Church, to accept Scripture completely, received the contraries as paradoxical. Just as the Trinity can be three in one or the hypostatic union can be two in one, everyone can be two if we rethink what we think we know about who we are—the individual, though etymologically and normally indivisible, is divisible after this life. With this understanding, an individual can be ultimately saved and unsaved, and Scripture’s paradox of salvation’s extent can be entirely true.